Thermal tolerance and preference are both consistent with the clinal distribution of house fly proto-Y chromosomes. Issue 5 (1st October 2021) - Delclos, Pablo J.; Adhikari, Kiran; Hassan, Oluwatomi; Cambric, Jessica E.; Matuk, Anna G.; Presley, Rebecca I.; Tran, Jessica; Sriskantharajah, Vyshnika; Meisel, Richard P.
Abstract: Selection pressures can vary within localized areas and across massive geographical scales. Temperature is one of the best studied ecologically variable abiotic factors that can affect selection pressures across multiple spatial scales. Organisms rely on physiological (thermal tolerance) and behavioral (thermal preference) mechanisms to thermoregulate in response to environmental temperature. In addition, spatial heterogeneity in temperatures can select for local adaptation in thermal tolerance, thermal preference, or both. However, the concordance between thermal tolerance and preference across genotypes and sexes within species and across populations is greatly understudied. The house fly, Musca domestica, is a well-suited system to examine how genotype and environment interact to affect thermal tolerance and preference. Across multiple continents, house fly males from higher latitudes tend to carry the male-determining gene on the Y chromosome, whereas those from lower latitudes usually have the male determiner on the third chromosome. We tested whether these two male-determining chromosomes differentially affect thermal tolerance and preference as predicted by their geographical distributions. We identify effects of genotype and developmental temperature on male thermal tolerance and preference that are concordant with the natural distributions of the chromosomes, suggesting that temperature variation across the species range contributes to the maintenance of the polymorphism. In contrast, female thermal preference is bimodal and largely independent of congener male genotypes. These sexually dimorphic thermal preferences suggest that temperature-dependent mating dynamics within populations could further affect the distribution of the two chromosomes. Together, the differences in thermal tolerance and preference across sexes and male genotypes suggest that different selection pressures may affect the frequencies of the male-determining chromosomes across different spatial scales.